EFL Learners’ Perspectives on Syntactic Awareness in Academic Writing - Ali, Sri Widyarti (Jurnal Riksa Cendikia Nusantara, 2026)
This study explores EFL learners’ perspectives on syntactic awareness in academic writing within an Indonesian higher education context. Although syntax is often taught as rule-based grammar, little attention has been given to how learners conceptualize and utilize syntactic awareness in their writing processes. Employing a qualitative case study design, data were collected through semi-structured interviews with 15 undergraduate students in an English Education program who had completed Academic Writing and English Syntax courses. The data were analyzed using thematic analysis. The findings reveal that learners perceive syntactic awareness as conscious attention to sentence structure, a strategy for achieving academic complexity, an error-monitoring mechanism, a bridge between grammatical knowledge and writing practice, a cognitive challenge, a product of reflective practice, a source of writing confidence, and a meaning-making resource. The study concludes that syntactic awareness extends beyond grammatical knowledge and functions as a dynamic metalinguistic and metacognitive process supporting academic literacy development. These findings highlight the importance of integrating reflective syntactic engagement into EFL writing pedagogy.